ANALISIS PENGETAHUAN KOMPETENSI KEPRIBADIAN DAN SOSIAL GURU PADA MAHASISWA PGSD UNIVERSITAS RIAU - Mega Wahyuni; M. Jaya Adiputra; Gustimal Witri (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2023)
Abstract: The purpose of this study was to find out how far the level of knowledge of teacher personality and social competencies possessed by PGSD students at the University of Riau as prospective educators. This research uses a descriptive method with a quantitative approach. The data analysis technique used in this discussion is a quantitative method, namely data analysis and interpretation techniques in the form of measuring quantitative data through scientific calculations. The results of this study indicate that the level of knowledge of personality competencies possessed by PGSD students at the University of Riau in the 2017 class was 80.56%, the 2018 class was 80.23%, and the 2019 class was 81.89%. While the average knowledge of social competence of PGSD University of Riau students class of 2017 was 80.85%, class of 2018 was 81.05% and class of 2019 was 87.22%. The highest average personality competency knowledge is owned by the 2019 class with a total of 81.89%. While the highest average social competency is owned by the 2019 class with a total of 87.22%. Key Words: Knowledge, Teacher Competence, Teacher Personality Competence, Teacher Social Competence